The fix : saving America from the corruption of a mob-style government - McQuade, Barbara (Seven Stories Press, 2026)
Explores the tactics of the far-right MAGA system, including information warfare, aggressive retribution, conformism enforced by fear, and perfasive dismantling of checks and balances, to dominate institutions and eliminate government accountability, and suggests common-sense reform to reclaim rul eof law and center democracy.